THE INFLUENCE OF WORK ENVIRONMENT, WORK ENTHUSIASM AND REWARDS ON WORK DISCIPLINE (LITERATURE REVIEW HUMAN RESOURCE MANAGEMENT) - Achmad Fauzi; Ribka Natalia; Kevin Sean; Kasman Abas; Maryanti Maryanti (Dinasti Publisher, 2022)
Human resources as the important resource which drive the organization. Human resources in company is the employees. Employees are required to have good discipline in order to achieve good performance. Work environment, work enthusiasm, and rewards are factors that increasing work discipline on employee. This literature study was conducted to determine the effect of the work environment, work enthusiasm, and rewards on work discipline. Literature studies are carried out to draw conclusions without having to conduct studies directly in the field. The independent variables in this study are work environment, work enthusiasm, and rewards, the dependent variable is work discipline. The results of this study indicate that a conducive work environment, enthusiasm for work, and the provision of rewards can support employees to improve work discipline.